Moscow Versus Leningrad: The Rivalry in the Cultural Field of the NEP Era (Based on the Archival Research in thе State Publishing House Collections) - Daria S. Moskovskaya (Литературный факт, 2025)
Archival research enables to reconstruct and present the history of the confrontation between the head office of Gosizdat in Moscow and Lengiz as its structural unit. The article shows that this conflict, which began in 1923, clearly manifested the “geographical factor” of the uneasy relations between the country’s power center and periphery, represented by the national republics, and Leningrad as the cultural center of the former empire. Using the example of several cultural institutions, the article concludes that in the formative period of Soviet statehood and the situation of the New Economic Policy, the construction of a power vertical required linking centralized management with the economic independence of regions and organizations to optimize the production process. Ultimately, the balance of cultural forces between the center and the periphery did not always work out in favor of the governing center. Archival documents prove that Lengiz conducted a more effective publishing policy, which determined his unwillingness to comply with the requirements of the head office in Moscow and obey its orders. The article establishes that in striving for commercial and financial independence, Lengiz was supported by the Leningrad Regional Executive Committee. The conflict between the head office of Gosizdat in Moscow and Lengiz reflected the general contradiction of the time between the value of cultural capital and the production goals of state construction, which devalued the importance of cultural heritage at that time.